An autecological study of the Marula (Sclerocarya birrea) in the Kruger National Park with specific reference to the relative impact from elephants and fire - Van Hoven, Wouter (University of Pretoria, 2013)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2007.